Uncovering the Changing Gene Expression Profile of Honeybee (Apis mellifera) Worker Larvae Transplanted to Queen Cells - Yin, Ling; Wang, Kang; Niu, Lin; Zhang, Huanxin; Chen, Yuyong; Ji, Ting; Chen, Guohong (Frontiers in Genetics, 2018)
Abstract The reproductive division of labor, based on caste differentiation in social insects, is of great significance in evolution. Generally, a healthy bee colony consists of a queen and numerous workers and drones. Despite being genetically identical, the queen and workers exhibit striking differences in morphology, behavior, and lifespan. The fertilized eggs and larvae selectively develop into queen and worker bees depending on the local nutrition and environment. Bee worker larvae that are transplanted within 3 days of age to queen cells of a bee colony can develop into queens with mature ovaries. This phenomenon is important to the understanding of the regulatory mechanisms of caste differentiation. In this study, we transplanted worker larvae (Apis mellifera) at the age of 1 (L1), 2 (L2), and 3 days (L3) into queen cells until the age of 4 d. Subsequently, genetic changes in these larvae were evaluated. The results revealed that the number of differentially expressed genes (DEGs) in L1 vs. L3 was more than that in L1 vs. L2. Furthermore, many of the genes that were downregulated are mostly involved in metabolism, body development, reproductive ability, and longevity, indicating that these functions decreased with the age of transplantation of the larvae. Moreover, these functions may be critical for worker larvae to undergo the developmental path to become queens. We also found that the DEGs of L1 vs. L2 and L1 vs. L3 were enriched in the MAPK, FoxO, mTOR, Wnt, TGF-beta Hedgehog Toll and Imd, and Hippo signaling pathways. Gene Ontology analysis indicated that some genes are simultaneously involved in different biological pathways; through these genes, the pathways formed a mutual regulatory network. Casein kinase 1 (CK 1)was predicted to participate in the FoxO, Wnt, Hedgehog, and Hippo signaling pathways. The results suggest that these pathways cross-talked through the network to modify the development of larvae and that CK 1 an important liaison. The results provide valuable information regarding the regulatory mechanism of environmental factors affecting queen development, thus enriching the understanding of bee caste differentiation.